(untitled) (Bangladesh Agronomy Journal, 2017)
An experiment was conducted at the Regional Agricultural Research Station, Ishwardi, Pabna in two consecutive years of 2010-2011 and 2011-2012 to quantify the effect of temperature on phenological duration and grain growth of wheat. Temperature variation was created by changing sowing date (15 November=S1, 30 November=S2, 15 December=S3 and 30 December=S4). Results revealed that reproductive phase was more sensitive to high temperature as compared to vegetative phase of wheat. Reproductive phase reduced from 54 to 37 days in 2010-2011 and from 64 to 34 days in 2011-2012 as influenced by higher air temperature under late sowing. Duration of reproductive phase was strongly and negatively correlated with mean air temperature (r=-0.64 to -0.96 at p<0.01). Maximum grain growth (49.12-50.18 mg grain-1) was recorded at 55 days after anthesis in 30 November sowing in both the years. Grain growth was negatively correlated (r=-0.80 at p<0.01) with mean air temperature during grain growth period. Grain yield was the highest (4560-6080 kg ha-1) in 30 November sowing, afterwards it reduced in both the years. Grain yield was negatively correlated (r=-0.70 at p<0.01) with mean air temperature of grain growth period. Rising of air temperature at grain filling stage subjected to reduced grain yield of wheat. Effect of temperature on grain yield of wheat can be explained about 88% by the function of Y= -14910+ 2069X-52.67X2 (R² = 0.88). Rising of one degree (oC) temperature above optimum (19.64 0C) grain yield reduced @ 53 kg ha-1 (0.98%). Bangladesh Agron. J. 2016 19(2): 79-85